An updated version of the computational package SIMPRE that uses the standard conventions for Stevens crystal field parameters. Issue 26 (4th August 2014) - Baldoví, José J.; Clemente‐Juan, Juan M.; Coronado, Eugenio; Gaita‐Ariño, Alejandro; Palii, Andrew
<x xml:space="preserve">Abstract</x> The crystal field approach used by SIMPRE is analyzed, verifying the exactness of the results concerning energy levels and magnetic properties calculated by the package. To coincide with the prevailing conventions, we reformulate the presentation of the crystal field parameters, so that the results are now, also from a formal point of view, strictly correct. New calculations are presented to test the influence of neglecting the excited J states, a common but critical approximation employed by SIMPRE. For that, we examine the case of Er(trensal) complex (H3trensal = 2, 2′, 2″‐tris(salicylideneimino)triethylamine) where the influence of this approximation is found to be minimal. A patched version of the code, SIMPRE 1.1, and an updated version of the user manual are now available. Finally, we comment on "Software package SIMPRE – revisited, " which apparently revisits a software package without inspecting or using the code. © 2014 Wiley Periodicals, Inc.